Identification of deep intronic individual variants in patients with hemophilia A by next‐generation sequencing of the whole factor VIII gene. Issue 2 (5th August 2017) - Inaba, Hiroshi; Shinozawa, Keiko; Amano, Kagehiro; Fukutake, Katsuyuki
Abstract: Essentials Intronic variants of the factor VIII gene ( F8 ) causing hemophilia A have been reported. We established an analysis method for whole F8 and investigated the variants within its introns. Rare variants located within introns of F8 in patients with hemophilia A are not uncommon. The c.6429+14194T>C variant was characteristically detected in patients with inversion. Background: No genetic defects are found in the coagulation factor VIII gene ( F8 ) of approximately 2% of patients with hemophilia A. Recently, genomic variants causative of hemophilia A that were located deep within introns have been reported. Objectives: We aimed to establish a comprehensive method of analysis of F8 using next‐generation sequencing (NGS) and investigate the variants located deep within the introns of F8 . Patients/Methods: Forty‐five male patients with hemophilia A, including 31 with previously identified causative mutations, were investigated. Results: Our NGS analysis allowed for the identification of genetic variants in roughly 99% of F8 . We confirmed that our NGS analysis can detect the single nucleotide variants and small deletions with high accuracy. After filtering, a total of 27 rare and unique individual variants from 16 patients remained. Three of these variants, c.144‐10810T>C, c.1010‐365A>G, and c.5219+9065A>G, were predicted as deleterious with high expected accuracy by PredictSNP2 analysis. We also predicted the impact on splicing by in silico analysis using three different algorithms. Two patients with unknown causative mutations carried unique individual variants, c.144‐10810T>C and c.6723+193G>A. We inferred that the c.144‐10810T>C variant likely causes hemophilia, while the effect of the c.6723+193G>A variant remains unclear. Our analysis showed that the c.6429+14194T>C variant was significantly detected in patients carrying the intron 22 inversion. Conclusions: Rare and unique individual variants located deep within the F8 introns in patients with hemophilia A are not uncommon. Future studies are necessary to determine the function and effect of these variants on F8 expression.